2D Layer Structure in Two New Cu(II) Crystals: Structural Evolvement and Properties - Jia-Jing Luo; Xiang-Xin Cao; Qi-Wei Chen; Ying Qin; Zhen-Wei Zhang; Lian-Qiang Wei; Qing Chen (Crystals, 2022)
Two new Cu(II) crystals, {[Cu(dtp)]·H2O}n (1) and [Cu(Hdtp)(bdc)0.5]n (2) (H2dtp = 4′-(3,5-dicarboxyphenyl)-2,2′:6′,2‴-terpyridine, H2bdc = 1,4-benzenedicarboxylic acid) were synthesized under hydrothermal conditions. X-ray single-crystal structural analysis revealed that the 5-connective Cu(II) is in a distorted tetragonal-pyramidal coordination sphere for both compounds. Crystal 1 shows a “wave-shaped” 2D layer in the structure, while 2 bears a 1D coordination chain structure and a supermolecular 2D layer structure with a thickness of 7.9 Å via 1D chain stacking. PXRD and TGA measurements showed that 1 and 2 are air stable, with thermal stabilities near 300 °C.